The Role of Knowledge Management On The Performance Of Coffee Company In Southeast Asian Countries: An Initial Meta-Analytic Review - Hendra Syahputra; Nur Edwar M (Proceedings of AICS - Social Sciences, 2016)
The objective of this paper is to review some researches on knowledge management, business environment as well as competitive strategies applied  in small and middle companies that will provide best practices for the improvement of performance of coffee processing company in ASEAN. This study consists of systematic reviews of 17 empirical scientific papers in regard to knowledge management, business environment, and competitive strategies that influence the performance of coffee processing company in ASEAN. Given the importance of the existence of coffee processing company in Indonesia, the application of knowledge management has to be prioritized by the concerned companies in order to accelerate their competitive advantages. This paper provides a better understanding on how to develop good knowledge management application, industry environment as well as strengthen the competitive strategies specifically in coffee processing company by learning from other sectors. The result of this study is believed to give worth understanding about actual situation in this field of research. It proposed some notions that will stimulate more intensive researches in this field in the future. However, there are no systematic literatures in academic journal that cover all the topics discussed in this paper.